An Efficient, Rapid, and Recyclable System for CRISPR-Mediated Genome Editing in Candida albicans - Nguyen, Namkha; Quail, Morgan M. F.; Hernday, Aaron D. (mSphere, 2017)
Candida albicans is the major fungal pathogen of humans and is the subject of intense biomedical and discovery research. Until recently, the pace of research in this field has been hampered by the lack of efficient methods for genome editing. We report the development of a highly efficient and flexible genome editing system for use with C. albicans . This system improves upon previously published C. albicans CRISPR systems and enables rapid, precise genome editing without the use of permanent markers. This new tool kit promises to expedite the pace of research on this important fungal pathogen. Candida albicans is the most common fungal pathogen of humans. Historically, molecular genetic analysis of this important pathogen has been hampered by the lack of stable plasmids or meiotic cell division, limited selectable markers, and inefficient methods for generating gene knockouts. The recent development of clustered regularly interspaced short palindromic repeat(s) (CRISPR)-based tools for use with C. albicans has opened the door to more efficient genome editing; however, previously reported systems have specific limitations. We report the development of an optimized CRISPR-based genome editing system for use with C. albicans . Our system is highly efficient, does not require molecular cloning, does not leave permanent markers in the genome, and supports rapid, precise genome editing in C. albicans . We also demonstrate the utility of our system for generating two independent homozygous gene knockouts in a single transformation and present a method for generating homozygous wild-type gene addbacks at the native locus. Furthermore, each step of our protocol is compatible with high-throughput strain engineering approaches, thus opening the door to the generation of a complete C. albicans gene knockout library. IMPORTANCE Candida albicans is the major fungal pathogen of humans and is the subject of intense biomedical and discovery research. Until recently, the pace of research in this field has been hampered by the lack of efficient methods for genome editing. We report the development of a highly efficient and flexible genome editing system for use with C. albicans . This system improves upon previously published C. albicans CRISPR systems and enables rapid, precise genome editing without the use of permanent markers. This new tool kit promises to expedite the pace of research on this important fungal pathogen.